Local Wisdom in The Process of Criminal Law Enforcement in Papua (Case Study Of Handling Criminal Actions Preceded By Traditional Fine In Wamena, Jayawijaya District) - Arsensius, Ricarda; Prasetyo, Handoyo; Wahyudi, Slamet Tri (PT. Hafasy Dwi Nawasena, 2024)
This study explores the integration of local wisdom into the criminal justice system in Papua, focusing on the handling of criminal actions in Wamena, Jayawijaya District. Papua's unique cultural context necessitates a nuanced approach to law enforcement, where traditional practices coexist with formal legal mechanisms. The research investigates how traditional fines, a form of customary penalty, are applied in conjunction with or as an alternative to state-imposed sanctions. The study employs a qualitative methodology, utilizing interviews, field observations, and analysis of legal documents to examine the procedural and cultural dynamics involved in these cases. It highlights the role of local wisdom in shaping legal outcomes and the impact of traditional practices on community perceptions of justice. Findings indicate that traditional fines, while sometimes seen as less formal or less effective than state penalties, play a crucial role in maintaining social harmony and resolving conflicts within the community. The research reveals that integrating these practices with formal legal procedures can enhance the effectiveness of the criminal justice system by ensuring that sanctions are culturally relevant and accepted by local populations. The study concludes that acknowledging and incorporating local wisdom into criminal law enforcement in Papua can lead to more culturally sensitive and effective justice practices. Recommendations include fostering greater collaboration between traditional leaders and formal legal institutions to create a more cohesive and culturally attuned legal framework.